Promosi Kesehatan dan Deteksi Dini Diabetes Melitus melalui Edukasi dan Pemeriksaan di Desa Bondalem, Tejakula, Buleleng - Gusti Ayu Tirtawati; I Nyoman Gejir; Hertog Nursanyoto; Dewa Ayu Agustini Posmaningsih (CV. ITTC INDONESIA, 2025)
The community service program entitled “Health Promotion and Early Detection of Diabetes Mellitus through Education and Screening in Bondalem Village, Tejakula, Buleleng” was implemented in response to the increasing incidence of diabetes mellitus (DM) and the low public awareness of early detection. The activities included health education, blood glucose screening, and training for village health cadres. A total of 30 participants enthusiastically joined the program. Pre- and post-test results showed an increase in participants’ knowledge from 23% to 87%, and 10% of participants were found to have elevated blood glucose levels. Ten trained village health cadres were empowered to continue health promotion independently. This program proved effective in improving community knowledge, strengthening early detection efforts for DM, and fostering the sustainability of community-based health initiatives through collaboration between academics, health workers, and local government.